Effects of Dietary Probiotic Supplementation on Egg Quality during Storage - Carvalho C.L. (2022)
© 2022 by the authors.The objective of this study was to evaluate whether probiotic supplementation to laying hens can improve the quality of eggs during storage. The trial was developed in a commercial farm, in which light-weight laying hens (36 weeks old) housed in cages were randomly selected for one of two different treatments: a control group fed non-supplemented diets, or birds fed with diets supplemented with 50 g/ton of probiotics. The trial lasted for 84 days, comprising three productive phases of 28 days each. The fresh egg quality was evaluated and then the eggs were stored and randomly separated for quality assessment at each storage interval (7, 14, 21, 28, 35, and 42 days). Means were compared using variance analysis considering differences at 5 and 10%. The probiotic was able to improve albumen weight, yolk length, yolk height, and yolk index (p < 0.05) during storage. Yolk color (fan) was also improved by 3.9% (p < 0.001), while increases of 1.35% (p < 0.001) in luminosity, 8.05% (p < 0.001) in red intensity, and 3.4% (p < 0.001) in yellow intensity were observed in comparison to the control group. Probiotic treatment was able to reduce by 2.03% (p < 0.001) yolk pH, and by 19.65% (p < 0.05) TBARS levels when compared to the control treatment. Therefore, the addition of probiotics to laying hen diets is an effective strategy to improve egg quality during storage.